KONTEKS PEMILIHAN KETUA KELAS PADA MATERI PERSENTASE: DESAIN PEMBELAJARAN DENGAN PENDEKATAN PMRI - Sari Saraswati; Andi Harpeni Dewantara (Didaktika : Jurnal Kependidikan, 2020)
This study aims at investigating how the context of class leader selection can support the fifth graders’ understanding of the percentage concept. The research method is design research which consists of 3 stages, namely preliminary design, teaching experiment and retrospective analysis. The research subjects involved fifth grade students at an elementary school in Palembang in which 6 students were in the pilot experiment and 25 students involved in the teaching experiment. Data were collected through tests, interviews, documentation and field notes. The results shows that the implementation of Realistic Mathematics Education (RME) approach using class leader selection context could create a more enjoyable and meaningful percentage learning. The resulting learning trajectory consists of two learning activities; playing the role of class leader election as well as the second round class leader election proved to be able to support students' understanding of the concept of percent from the informal level to the formal level.Keywords: percentage; PMRI; class leader election